2010
DOI: 10.1186/1746-4811-6-5
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and robust assay for detection of S-phase cell cycle progression in plant cells and tissues by using ethynyl deoxyuridine

Abstract: BackgroundProgress in plant cell cycle research is highly dependent on reliable methods for detection of cells replicating DNA. Frequency of S-phase cells (cells in DNA synthesis phase) is a basic parameter in studies on the control of cell division cycle and the developmental events of plant cells. Here we extend the microscopy and flow cytometry applications of the recently developed EdU (5-ethynyl-2'-deoxyuridine)-based S-phase assay to various plant species and tissues. We demonstrate that the presented pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 30 publications
2
133
0
Order By: Relevance
“…10 Important and surprisingly, sensitive 5-ethynyl-2 0 -deoxyuridine (EdU) labeling for detection of tuber nuclei that were wound-induced to synthesize DNA showed that de novo DNA synthesis occurred with a maximum number of nuclei induced into the S-phase of the cell cycle by 18 h after wounding (Table 1). 11,12 The number of nuclei in the S-phase rapidly decreased and was near zero by 48 h after wounding; this was roughly 5 d prior to the creation of a nascent phellogen and induction of cell division as a distinguishing part of wound periderm biosynthesis. This period of DNA biosynthesis translates to about 30 h in which induced cells progress through the S-phase with cessation of DNA biosynthesis about 4 d prior to completion of CLF and about 5 d prior to initiation of cell division and associated WPF.…”
Section: Biological Processes Associated With Closing Layer Formationmentioning
confidence: 99%
“…10 Important and surprisingly, sensitive 5-ethynyl-2 0 -deoxyuridine (EdU) labeling for detection of tuber nuclei that were wound-induced to synthesize DNA showed that de novo DNA synthesis occurred with a maximum number of nuclei induced into the S-phase of the cell cycle by 18 h after wounding (Table 1). 11,12 The number of nuclei in the S-phase rapidly decreased and was near zero by 48 h after wounding; this was roughly 5 d prior to the creation of a nascent phellogen and induction of cell division as a distinguishing part of wound periderm biosynthesis. This period of DNA biosynthesis translates to about 30 h in which induced cells progress through the S-phase with cessation of DNA biosynthesis about 4 d prior to completion of CLF and about 5 d prior to initiation of cell division and associated WPF.…”
Section: Biological Processes Associated With Closing Layer Formationmentioning
confidence: 99%
“…Triton X-100 treatment results in a nuclear stain and is compatible with EdU costaining. Moreover, it prevents the cell shrinkage and quick penetration of the fixer and allows better preservation of mitotic stages (Kotogány et al, 2010).…”
Section: Edu-based Dna Synthesis and Cell Proliferation Assaymentioning
confidence: 99%
“…A key benefit of using EdU is that a heat or acid denaturation step is not required for immunoprecipitation (reviewed in Darzynkiewicz et al, 2011). Hence, it is possible to visualize EdU-labeled DNA while maintaining native subnuclear structure (Kotogany et al, 2010;Bass et al, 2014) and to separate labeled from unlabeled nuclei by flow cytometry prior to DNA isolation . We previously used the EdU labeling system to investigate the spatio-temporal aspects of DNA replication in proliferating root tip cells (Bass et al, 2015).…”
Section: Introductionmentioning
confidence: 99%